The complete guide to cardiac CT - Abramson, Simeon (McGraw-Hill, 2012)
"Based on the popular review courses of educator and radiologist Dr. Simeon Abramson, The Complete Guide to Cardiac CT is a timely, hands-on learning tool--one that will help you master every important aspect of cardiac CT, from acquisition to interpretation. This unique guide translates complex concepts and topics into understandable, relevant subject matter and includes contributions from international leaders in cardiac CT. Designed for the practical, day-to-day application of cardiac CT, the text also serves as a comprehensive visual resource more than 1000 laser-precise images and illustrations, all of which reflect the latest clinical acumen and cardiac imaging technology."--Publisher's website.